Placebo From an Enactive Perspective - Arandia, Iñigo R.; Di Paolo, Ezequiel A. (Frontiers in Psychology, 2021)
Due to their complexity and variability, placebo effects remain controversial. We suggest this is also due to a set of problematic assumptions (dualism, reductionism, individualism, passivity). We critically assess current explanations and empirical evidence, and propose an alternative theoretical framework—the enactive approach to life and mind—based on recent developments in embodied cognitive science. We review core enactive concepts such as embodiment, agency, and sense-making. Following these ideas we suggest moving from binary distinctions (e.g., conscious vs. nonconscious) to the more workable categories of reflective and pre-reflective activity. We introduce an ontology of individuation, following the work of Gilbert Simondon, that allows us to see placebo interventions not as originating causal chains, but as modulators and triggers in the regulation of tensions between ongoing embodied and interpersonal processes. We describe these interrelated processes involving looping effects through three intertwined dimensions of embodiment: organic, sensorimotor, and intersubjective. Finally, we defend the need to investigate therapeutic interactions in terms of participatory sense-making, going beyond the identification of individual social traits that contribute to placebo effects. We discuss resonances and differences between the enactive proposal, popular explanations such as expectations and conditioning, and other approaches based on meaning responses and phenomenological/ecological ideas.